The Use of Public Opinion Surveys as a Political Instrument - Quiroz Vera, Eduardo Fernando (2005)
This article aims to offer a theoretical reflection on the scope of public opinion polls. Although it is evident that its widespread use derives from its instrumental nature, little has been explored in our environment about the political nature that underlies the use of this mechanism.